Real-world effectiveness and persistence of reference etanercept versus biosimilar etanercept GP2015 among rheumatoid arthritis patients: A cohort study - Carballo, Nuria; Pérez García, Carolina; Grau, Santiago; Monfort, Jordi; Durán-Jordà, Xavier; Echeverría-Esnal, Daniel; Ferrández, Olivia (Frontiers in Pharmacology, 2022)
Although several randomized clinical trials have confirmed that there is no difference in efficacy between etanercept and its biosimilar versions in the treatment of rheumatoid arthritis (RA), limited real-world evidence is available. We conducted a cohort study to compare the effectiveness and treatment persistence between the reference etanercept(ETN) and the biosimilar GP2015 in RA patients in a real-life setting. Adults with a diagnosis of RA who initiated treatment with ETN or GP2015, between January2007 and December2019, were included. The follow-up period was 52weeks. The primary outcome was the mean of change in the DAS28-CRP values and the adjusted mean difference from baseline to 52 weeks between ETN and GP2015. Other effectiveness endpoints assessed were the rate of patients who achieved remission or low disease activity (LDA) at week52, who showed a reduction of DAS28-CRP value greater than or equal to 1.2 from baseline to week52 and rate of good responder patients (those meeting both effectiveness measures) at week 52. Treatment effectiveness over time (baseline, 26 and 52 weeks) was compared between the ETN and GP2015 groups using mixed effects models. Treatment persistence (probability of maintaining the same treatment over time) was also evaluated and shown using Kaplan–Meier survival curves. A total of 115 RA patients were included(ETN, n=90; GP2015, n=25). No differences were observed in the primary outcome: DAS28-CRP score decreased from baseline to week 52 [5.1 to 2.7 (mean of change -2.37) in ETN group and 5.0 to 2.2(mean of change -2.84) in GP2015 group, p-value=0.372] and the adjusted mean difference was −0.37(−1.03 to 0.29). No differences were also observed in the other effectiveness endpoints assessed among patients treated with ETN or GP2015: rate of patients who achieved remission(54.1% vs 66.7%, p-value=0.303) and LDA (71.6% vs 80.9%, p-value=0.391) at week 52, reduction of DAS28-CRP value greater than or equal to 1.2 from baseline to week 52(75.6% vs 80.9%, p-value=0.613) and rate of good responder patients(58.1% vs 76.1%, p-value=0.202). Drug survival was 82% and 80% for ETN and GP2015, respectively (log-rank p-value). Etanercept and its biosimilar GP2015 show similar effectiveness and treatment persistence in RA patients in a real-life setting.